Academic Self-Efficacy Beliefs of Pre-Service Elementary School Teacher Candidates. (13th May 2015) - Sarıcoban, Gulay
Abstract: The purpose of this study is to examine the self-efficacy beliefs of pre-service elementary school teacher candidates with special reference to their gender. To do so, Academic Self-efficacy Scale (ASE) adapted fromOwen and Froman (1988) and used byEkici (2012) was used. The questionnaire was conducted in Turkish for clarity, the translation of which was done by language specialists (Ekici, 2012 ). The overall reliability of the scale for Turkish version has been found .86. It is .88 for SS, .82 for CA, and .90 for TS. As for the difference in gender, independent sample t-test was utilized. The results have indicated that they have almost positive attitudes towards their self-efficacies in their academic studies. Gender is not a significant factor in academic self-efficacy beliefs of pre-service elementary school candidate teachers. Lastly, to see if the participants differ in their opinions on academic self-efficacy with regard to their age range, One-way Anova was used. The results indicated that they also do not differ in this issue.